Pedagogical Applications, Prospects, and Challenges of Blended Learning in Chinese Higher Education: A Systematic Review - Ashraf, Muhammad Azeem; Mollah, Shorif; Perveen, Shahnaz; Shabnam, Nadia; Nahar, Lizoon (Frontiers in Psychology, 2022)
In recent years, blended learning (BL) has grown to occupy an important space in Chinese educational practice. Policymakers have developed many application strategies and platforms and are continuing to develop BL for future use. In order to apply BL in practice, key stakeholders have been using different Learning Management Systems (LMS), digital platforms, games, hybrid courses, and various forms of social media to create a framework for blended learning. The current study asserts that many visible opportunities have emerged in Chinese higher education through the applications of blended learning. The advantages of BL are that it fosters stronger academic achievement, student engagement, and cognitive engagement and understanding as well as flexible and quick communication skills, faster interaction skills, technical skills, and adaptability to ever-changing educational practices. On the other hand, BL has brought about some pedagogical and technical difficulties for both learners and practitioners. This study found that most BL courses are not as effective as they could be because they do not have a strong pedagogical framework. Moreover, BL suffers from the technical incompetence of teachers and students, the inefficiency of LMS, and the unavailability of required resources, such as certain devices and the Internet. Some higher education institutions have become pioneers in Chinese educational practice and been able to successfully adopt blended learning frameworks and integrate Moodle as well as other platforms and techniques. However, many other institutions’ attempts to adopt blended learning approaches have not been as effective. In order to better understand how and in what ways blended learning is being integrated into the educational system, this study overviews the current situation and discusses the strengths and weaknesses of blended learning in Chinese higher education.